2016
DOI: 10.1111/hel.12324
|View full text |Cite
|
Sign up to set email alerts
|

The internalization of Helicobacter pylori plays a role in the failure of H. pylori eradication

Abstract: The results showed that H. pylori invasion of the gastric epithelia might play a role in eradication failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
0
28
0
1
Order By: Relevance
“…Such a process might be a strategy for H. pylori to escape immune surveillance and remain alive in vivo (Amieva et al, 2002; Dubois and Borén, 2007), and it contributes to the complication of eradication. To determine whether H. pylori internalization plays a role in treatment failure, one study (Wang et al, 2016) carried out in our laboratory applied an invasion assay to evaluate the levels of H. pylori invasion of GES-1 cells. The results showed that the internalization levels of the failing strains were higher than those of the successful strains.…”
Section: Cellular Invasion Of H Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…Such a process might be a strategy for H. pylori to escape immune surveillance and remain alive in vivo (Amieva et al, 2002; Dubois and Borén, 2007), and it contributes to the complication of eradication. To determine whether H. pylori internalization plays a role in treatment failure, one study (Wang et al, 2016) carried out in our laboratory applied an invasion assay to evaluate the levels of H. pylori invasion of GES-1 cells. The results showed that the internalization levels of the failing strains were higher than those of the successful strains.…”
Section: Cellular Invasion Of H Pylorimentioning
confidence: 99%
“…The results showed that the internalization levels of the failing strains were higher than those of the successful strains. However, there is no consensus regarding whether the level of internalization is related to antibiotic resistance, with some studies considering that resistant strains are associated with significantly higher internalization activity than susceptible strains (Lai et al, 2006) but Wang et al (2016) reporting no evidence of this. Regardless of the correlation, once therapy fails, more consideration should be given to H. pylo ri internalization activity.…”
Section: Cellular Invasion Of H Pylorimentioning
confidence: 99%
“…They consist of a PPI plus three antimicrobials: metronidazole, tetracycline, and bismuth in the first therapy and metronidazole, amoxicillin, and clarithromycin in the second one [14,15]. These last regimens seem the most effective ones to overcome antibiotic resistance, the main proposed reason of treatment failure together with low patient compliance to therapy, high gastric bacterial load, cytochrome P450 polymorphism (CYP2C19), and high gastric acidity [16]. Antibiotic resistance to Hp has been suggested to arise from point mutations, drug inactivation, the activation of drug efflux pumps, altered membrane permeability, biofilm formation or the presence of bacterial dormant forms [17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this regimen is unacceptable as a first-line therapy for H. pylori (Graham and Fischbach, 2010). Several factors are involved in failed H. pylori eradication, including improper regimens, poor patient compliance, massive gastric bacterial loads, internalizing bacteria, high gastric acidity, gene polymorphisms (IL-1B and CYP2C19), antimicrobial washout and dilution, biofilm formation, and most importantly, resistance to antibiotics (Graham and Dore, 2016; Malfertheiner et al, 2016; Wang et al, 2017). During recent decades, the rate of antibiotic resistance (particularly to clarithromycin) has rapidly increased in most countries around the world (Thung et al, 2016).…”
Section: Introductionmentioning
confidence: 99%